Neonatal Seizures—Are We there Yet? - Ramantani, Georgia; Schmitt, Bernhard; Plecko, Barbara; Pressler, Ronit M.; Wohlrab, Gabriele; Klebermass-Schrehof, Katrin; Hagmann, Cornelia; Pisani, Francesco; Boylan, Geraldine B. (Neuropediatrics, 2019)
Neonatal seizures are the most prevalent and distinctive sign of neurologic dysfunction in early life and pose an immense challenge for clinicians. Improvements in neonatal care have increased the survival rate of extremely premature infants, considerably changing the spectrum of underlying etiologies, and instigating a gradual shift from mortality to morbidity. Recognizing neonatal seizures can be challenging due to variability in presentation but clinical features can often provide valuable clues about etiology. Yet, the majority of neonatal seizures are subclinical. Even though conventional electroencephalography (EEG) with simultaneous video detection of seizures still represents the diagnostic gold standard, continuous monitoring using a one- to two-channel amplitude-integrated EEG with concurrent unprocessed EEG can be crucial for early recognition and intervention. Furthermore, tremendous progress has been made in neuroimaging, and all infants with seizures should have a magnetic resonance imaging (MRI) to help identify the underlying etiology. While the majority of neonatal seizures are caused by hypoxic-ischemic events, stroke, hemorrhage, or infection, approximately 15% of patients will require more sophisticated algorithms for diagnostic workup, including metabolic and genetic screening. These recent developments have led to renew interest in the classification of neonatal seizures, which aim to help identify etiology and guide appropriate therapeutic and prognostic decisions. In this review, we outline recent progress made in the etiology, diagnosis, and treatment of neonatal seizures and highlight areas that deserve further research.
Keywords: neonatal seizures; outcome; preterm; term neonates